Mahabbah Teaching And The Problem Of Religious Moderation - Nani Widiawati (Fakultas Agama Islam Universitas Wiralodra, 2023)
Religious radicalism is related to misunderstandings in understanding the essential meaning of sacred texts so that religion appears to contradict the essence of the teachings it carries. This study aims to harmonize the values ​​of moderation in the concept of mahabbah as the core of Sufism teachings into religious practice. The results of the study show that the Mahabbah teachings offer moderate, humanist, and universal ideas. In the context of religious relations, the teachings of mahabbah erode egoism, strengthen harmony, release formal ties, and give birth to an open attitude to differences. Through the teachings of mahabbah, religion rediscovers its essential function and becomes a solution to the problem of religious radicalism.